(untitled) (Medico Legal Update, 2020)
Carbapenems are the drugs of choice against serious infections caused by Gram-negative bacteria Carbapenem-resistant. Acinetobacterbaumannii (CRAB) represents one of the important causing agents of nosocomial infections especially in immunocompromised and Intensive Care Units (ICUs) patients. The aim of this work was to identify the Carbapenem-Resistant genes in Acinetobacterbaumannii isolated from Baghdad and Ramadi hospitals. Among 48A. baumannii isolates, 33 isolates (68.75%) were resistant to imipenem and meropenem. One gene for carbapenem resistance (blaOXA-51 like) were amplified by PCR. The presence of blaOXA-51-like genes in 100% of CRAB isolates indicated that the blaOXA-51-like genes are the predominant mechanism for imipenem resistance in our isolates.